Tuning the morphology of ZnMn2O4 lithium ion battery anodes by electrospinning and its effect on electrochemical performance - Teh, Pei Fen (2013)
ZnMn2O4 structures of various morphologies (nanorods, nanofibers, nanowebs) have been prepared via a facile electrospinning technique by a simple variation of the sintering profile, and have subsequently been employed as anodes in lithium ion battery applications. After the sintering process, as-spun nanofibers with high aspect ratio have broken into short segments of ZnMn2O4 nanorods (ZMO-NR). Incorporating an intermediate carbonization step has strengthened the mechanical integrity of as-spun nanofibers, resulting in the formation of sintered nanofibers (ZMO-NF) and nanowebs (ZMO-NW). On the basis of FESEM, HRTEM and XRD studies, the formation mechanism of nanostructures consisting of hierarchically self-assembled ZnMn2O4 nanocrystals is discussed. Particle size distribution is computed by Rietveld refinement and HRTEM micrographs, while the valence states are confirmed by XPS. The initial discharge of ZMO-NF and ZMO-NW demonstrated a high capacity of ~1469 mA h g−1 and 1526 mA h g−1, respectively, in the voltage ranges of 0.005 V and 3.0 V versus Li/Li+ at 60 mA g−1, associated with reversible capacities of ~705 mA h g−1 and 530 mA h g−1 after 50 cycles. Morphology tuning of anodes and the importance of interconnected nanoparticulate pathways for lithium ion diffusion are elucidated.